Contextos de vulnerabilidade e de risco para a doença de Chagas, hanseníase e esquistossomose nas vilas produtivas rurais do projeto de integração do rio São Francisco no estado do Ceará - Silva Filho, José Damião (2024)
Introduction: The implementation of major water projects, such as the São Francisco River Integration Project (PISF), can have a series of negative impacts and may facilitate the emergence and spread of diseases that were previously not endemic in these regions. In this scenario, there is a risk of an increase in the incidence of Neglected Tropical Diseases (NTDs), such as schistosomiasis, Chagas disease and leprosy, considering the associated burden of morbidity and mortality, especially in the Northeast region, and the perpetuation of these diseases as a public health problem, which creates the challenge of defining strategic surveillance and control actions in the areas directly affected by this project. Objective: To analyze the contexts of vulnerability and risk for Chagas disease, leprosy and schistosomiasis in the productive rural villages (PRV) of the São Francisco River Integration Project in the state of Ceará. Methods: Descriptive cross-sectional study in the municipalities of Jati, Brejo Santo and Mauriti based on different strategies: 1-survey for diagnosis (schistosomiasis, Chagas disease and leprosy); 2- malacological and entomological survey; 3- knowledge of health professionals about aspects related to these NTDs and related health services, in the context of a training process. Results: The estimated prevalence of schistosomiasis was 0.97% (2/206) by the Kato-Katz method and 11.54% (27/234) by the POC-CCA immunochromatographic test; for Chagas disease 0.27% (1/368); and 2.7% (8/300) of suspected cases for leprosy were identified by dermatoneurological examination, but none confirmed. 21 water collections were investigated and 765 specimens of Biomphalaria sp. were found, most of them Biomphalaria straminea, none infected with Schistosoma mansoni. Of the 245 household units investigated (PRV Ipê in Jati - 14 houses; PRV Descanso in Mauriti - 77 houses; and PRV Vassouras in Brejo Santo - 154 houses), specimens of Triatoma pseudomaculata and Panstrongylus megistus were found in 4 (1.63%), but none with Trypanosoma cruzi. About health professionals (11 Community Health Workers, 10 Endemic Disease Control Workers and 10 coordinators/managers), in general there was a lack of knowledge about the diseases in various dimensions, partly related to the lack of access to educational/informational materials and training, but also to the current performance of non-healthcare functions. Conclusions: The municipalities evaluated in this study are areas of epidemiological importance for the transmission of schistosomiasis, Chagas disease and leprosy in the state of Ceará. Evidence generated here (verification of the presence of vectors, intermediate hosts and parasites that cause these diseases) provides elements that point to the need to implement control policies, in particular the strengthening of Primary Health Care. This highlights the importance of developing agendas with an intersectoral approach to tackle the problem from a One Health perspective and the strategic development of effective interventions in the areas covered by this project.